1998
DOI: 10.1021/jf980049c
|View full text |Cite
|
Sign up to set email alerts
|

Olive Oil Phenols and Their Potential Effects on Human Health

Abstract: Olive oil is the fat of choice in the Mediterranean area, where the diet has been associated with a lower incidence of coronary heart disease and certain cancers. Phenols in extra virgin olive oil are responsible for its peculiar pungent taste and for its high stability. Recent findings demonstrate that olive oil phenolics inhibit oxidation of low-density lipoproteins (the most atherogenic ones) and possess other potent biological activities that if demonstrated in vivo, could partially account for the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
226
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 356 publications
(244 citation statements)
references
References 31 publications
5
226
0
7
Order By: Relevance
“…It has been found that diets containing olive oil phenols may increase in vivo resistance of LDLs to oxidation; the effectiveness of oleuropein has been explained in part through its ability to act as an antioxidant and in part through a hypocholesterolaemic effect [61]. In an investigation by Coni et al [62] it was found that when fed a diet rich in oleuropein to rabbits, the ability of LDL to resist to oxidation increased, thanks to its antioxidant capacity; moreover, they found a significant reduction of the plasmatic levels of total, free and ester-derivatives of cholesterol.…”
Section: Health Aspects Linked To Phenols In Voomentioning
confidence: 99%
“…It has been found that diets containing olive oil phenols may increase in vivo resistance of LDLs to oxidation; the effectiveness of oleuropein has been explained in part through its ability to act as an antioxidant and in part through a hypocholesterolaemic effect [61]. In an investigation by Coni et al [62] it was found that when fed a diet rich in oleuropein to rabbits, the ability of LDL to resist to oxidation increased, thanks to its antioxidant capacity; moreover, they found a significant reduction of the plasmatic levels of total, free and ester-derivatives of cholesterol.…”
Section: Health Aspects Linked To Phenols In Voomentioning
confidence: 99%
“…The phenol concentration in olive oil depends on variety, climate, area of growth, latitude, and ripeness of the olive. The phenols, and in particular the orthodiphenols, have been demonstrated to contribute considerably to the oxidation stability of the oil (Gutfinger, 1981;Papadopoulos & Boskou, 1991;Rice-Evans et al, 1996;Visioli & Galli, 1998). Ortho-diphenols are the phenols with two adjacent hydroxyl groups to the ring structure: hydroxytyrosol and oleuropein and its derivatives (Figure 1 Figure 1 Structures of phenols present in olives and olive oil, their degradation into aglycones during ripening, and hydrolysis of aglycones into tyrosol and hydroxytyrosol.…”
Section: Chemistry and Content Of Phenols In Olive Oilmentioning
confidence: 99%
“…The world consumption of this product is significantly increasing in recent years and this positive trend is related not only to its nutritional and healthpromoting characteristics (Kiritsakis, 1998;Manna et al, 1997;Monteleone et al, 1998;Ranalli et al, 1997;Visoli and Galli, 1998;Mili, 2006;Waterman and Lockwood, 2007;Dag et al, 2011) but also to its sensory properties. In fact, the right balance among saturated, monounsaturated and polyunsaturated fatty acids, along with the significant presence of "minor" components such as aromatic phenolics and tocopherolic compounds (Lazzez et al, 2008;Dag et al, 2011) largely justify its commercial success (Fregapane and Salador, 2013).…”
Section: Introductionmentioning
confidence: 99%